2014
DOI: 10.2494/photopolymer.27.645
|View full text |Cite
|
Sign up to set email alerts
|

Novel EUV Resist Materials Design for 14 nm Half Pitch and below

Abstract: Polymers with a different Tg and activation energy were prepared to clarify influences of acid diffusion on resolution at 15 nm half-pitch (hp) and 14 nm hp using a EUV micro-field exposure tool (MET) at LBNL. Resolution on such a narrow pattern was limited by collapse and pinching. Clear relationship between pinching numbers and polymer Tg indicates that acid diffusion is one of major contributors on the pinching. In addition, polymers with a low thermal activation energy (Ea) on deprotection were effective f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Outgassing of resists has drawn much attention due to its impact on throughput and damages to optics. Several studies have been reported that polymer resists with low thermal activation energy upon deprotection are liable to outgassing. , Our previous work has revealed that the outgassing is primarily from the protecting groups and the skeleton is stable almost without outgassing under the EUV exposure . Therefore, the effects of different acid labile pendant groups on outgassing of the MG resists is essential for the molecule design.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Outgassing of resists has drawn much attention due to its impact on throughput and damages to optics. Several studies have been reported that polymer resists with low thermal activation energy upon deprotection are liable to outgassing. , Our previous work has revealed that the outgassing is primarily from the protecting groups and the skeleton is stable almost without outgassing under the EUV exposure . Therefore, the effects of different acid labile pendant groups on outgassing of the MG resists is essential for the molecule design.…”
Section: Resultsmentioning
confidence: 99%
“…The higher PEB temperatures for SP-AD and SP-BU resists further confirmed the hypothesis. The results are consistent with previous study about the relationship between E a and outgassing, suggesting that a low E a resist tends to release volatile species due to its high thermal reactivity even at room temperature.…”
Section: Resultsmentioning
confidence: 99%
“…A significant improvement in the resolution has been expected for EUV lithography because of the reduction in the wavelength. The resolution of EUV lithography with chemically amplified resist processes has already reached the sub-16-nm region [5,6]. The focus of the resist development is shifting to the 11-nm half-pitch node.…”
Section: Introductionmentioning
confidence: 99%
“…The biggest challenges for the successful implementation of EUVL for leading-edge logic devices and likely for futuristic fab-out DRAM, is the unavailability of compatible defect-free photoresists and mechanistic rapport to the scaling of feature size down to single-digit resolution 12 , 17 19 Note that there is no program to make through the direct write (maskless) tools, including electron beam lithography (EBL) 20 26 and helium ion beam lithography (HIBL) for mass production of IC chips to date 20 , 27 29 It suggests maskless tools can be used to counter the scarcity of rarely accessible EUV tools to resist developers for screening/prototyping of the futuristic logic nodes resists and low-volume production.…”
Section: Introductionmentioning
confidence: 99%